1990
DOI: 10.1002/bdd.2510110107
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation of the food effect: Transient changes in hepatic blood flow and michaelis‐menten parameters as mediators of hepatic first pass metabolism and bioavailability of propranolol

Abstract: A physiological model of propranolol disposition was designed to help explain the large increase in AUC seen when the drug is administered with food. The mass balance equation for the liver compartment used Michaelis-Menten terms to describe hepatic metabolism. Previously published pharmacokinetic and physiological parameters were used throughout. The three parameters, Qh, Kmt, and Vmax, were varied for different durations and by a factor of two to increase AUC. The parameter variations were patterned after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The relationship between C max and dose in Figure 2 was similar to that observed in the reference study8 for the propranolol C max . The power curve parameters are presented in Table 2.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The relationship between C max and dose in Figure 2 was similar to that observed in the reference study8 for the propranolol C max . The power curve parameters are presented in Table 2.…”
Section: Resultssupporting
confidence: 82%
“…Parameter values from a recent referenced study8 were used for the simulations for propanolol and presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is welldocumented that, after an oral administration, the portal vein drug concentration can be an order of a magnitude higher than that of a peripheral vein. 20 This high concentration of drug entering the liver can temporarily saturate metabolic enzymes and/or tissue binding sites. Using a computer simulation, Semple et al 20 have shown that a highly extracted drug such as propranolol behaves like a low-extraction drug during absorption.…”
Section: Discussionmentioning
confidence: 99%
“…20 This high concentration of drug entering the liver can temporarily saturate metabolic enzymes and/or tissue binding sites. Using a computer simulation, Semple et al 20 have shown that a highly extracted drug such as propranolol behaves like a low-extraction drug during absorption. This phenomenon may explain why nonlinear kinetics occurs in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…14 Indeed, a transient change in the maximal rate of metabolite formation is a likely cause of the food effect, and it has been postulated that this is mediated via hormonal responses to feeding. 28 The food effect is not caused by increased absorption since the drugs in question are completely absorbed in the fasting state and also because there is no effect on the levels of the metabolites.…”
Section: Discussionmentioning
confidence: 99%